THE IMPORTANCE OF ARGON LASER COAGULATION IN THE TREATMENT OF DIABETIC RETINOPATHY - Abdullaeva Sarvinoz Mukhammadbobur qizi; Abdullaev Shakhzodbek Oybek ugli (Web of Journals Publishing, 2024)
Diabetes mellitus and its complications are one of the most important medical, social and economic problems of modern healthcare. In the structure of disability and mortality of patients suffering from diabetes, the leading position is given to its late complications. Since their likelihood increases with increasing life expectancy, this problem is very relevant, especially if we take into account the preventive focus of modern diabetology.
Keywords: diabetic retinopathy, laser coagulation, visual acquity.